2014
DOI: 10.2131/jts.39.645
|View full text |Cite
|
Sign up to set email alerts
|

How does airway exposure of aflatoxin B1 affect serum albumin adduct concentrations? Evidence based on epidemiological study and animal experimentation

Abstract: -Aflatoxin B1 (AFB1) airway inhalation represents an additional route of exposure to this toxin. However, the association between AFB1 inhalation and serum AFB1 albumin adducts remains unclear. The aim of this study was to explore the association between airway exposure to AFB1 and serum AFB1 albumin adduct concentrations via an epidemiological study, as well as in an AFB1 airway exposure animal model. Our epidemiological study was conducted in a sugar factory in the Guangxi Autonomous Region of China. In orde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 32 publications
(43 reference statements)
0
4
1
Order By: Relevance
“…However, and contrary to previous published articles (Viegas et al, 2012c(Viegas et al, , 2013a(Viegas et al, , b, 2015Mo et al, 2014) we cannot state that exposure is occurring only by inhalation since the workers enrolled in this study are from different workplaces conditions in the same slaughterhouse. Regarding the specific case of evisceration workplace, where eight workers obtained results higher than the LOD, and since there is a low particle contamination in the air (data published elsewhere), exposure can be occurring by dermal absorption contrary to other situations already reported in different settings (Viegas et al, 2013a(Viegas et al, , b, 2015Mayer et al, 2012).…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…However, and contrary to previous published articles (Viegas et al, 2012c(Viegas et al, , 2013a(Viegas et al, , b, 2015Mo et al, 2014) we cannot state that exposure is occurring only by inhalation since the workers enrolled in this study are from different workplaces conditions in the same slaughterhouse. Regarding the specific case of evisceration workplace, where eight workers obtained results higher than the LOD, and since there is a low particle contamination in the air (data published elsewhere), exposure can be occurring by dermal absorption contrary to other situations already reported in different settings (Viegas et al, 2013a(Viegas et al, , b, 2015Mayer et al, 2012).…”
Section: Discussioncontrasting
confidence: 76%
“…The main objective was to obtain data regarding recent exposure to AFB1 and also its level of intensity. This approach is useful for rapid screening for acute exposures and also reflects chronic exposure (Viegas et al, 2012c(Viegas et al, , 2013a(Viegas et al, , b, 2015Leong et al, 2012;Mo et al, 2014).…”
Section: Slaughterhouse Studiedmentioning
confidence: 99%
“…However, in the same study, mycotoxins were not detected in air samples collected in the same facilities (active sampling methods) [49]. Thus, the use of passive sampling methods such as settled dust appears to be the best option for mycotoxins assessment in occupational environments [18,50,51]. Interestingly, settled dust did not show any fungal growth supporting the evidence that the indoor presence of fungal species does not imply the exposure to mycotoxins and vice versa.…”
Section: Overview Of Studies Developed In Portugal (2012-2020)mentioning
confidence: 61%
“… Lai et al (2014) observed an elevated risk of hepatocellular carcinoma (HCC) for sugar and papermaking workers with airway exposure to Aspergillus flavus-contaminated dust respect to controls. In similar working environments, low-dose exposure to AFB1 was associated with lung cancer while heavy and prolonged exposure to airway AFB1 may be complicated by the development of lung cancer and HCC ( Mo et al 2014 ).…”
Section: Resultsmentioning
confidence: 99%